PENGARUH KONSELING FARMASIS DALAM MENINGKATKAN KEPATUHAN PASIEN DIABETES MELITUS MENGGUNAKAN OBAT ANTIDIABETES DI PERUM KETAPANG SOKARAJA KULON - Ikhwan Yuda Kusuma (Viva Medika, 2018)
ABSTRACT The WHO survey results show that the number of DM patients in Indonesia is ranked the 4th largest in the world. DM causes death by 5% every year. Deaths from DM are expected to increase by 50% in the next ten years. The results of the 2007 Central Java RISKESDAS showed that the prevalence of DM in Central Java province was 0.8% and overall was 1.3%. The highest prevalence is found in Cilacap Regency (3.9%), second place is Tegal City Regency (3.1%), for the third place is Surakarta (2.8%), fourth place is Pemalang (2.1%), and fifth place is occupied by Banyumas (1.9%) (Ministry of Health, 2009). This study used an experimental design by treating the group of cases. The research instruments in this study were interview guides about the number of remaining antidiabetic drugs to check the compliance and MMAS questionnaires that had been validated and translated into Indonesian versions (Setyaningsih, 2013). The results of the data analysis using the Chi-Square test were obtained p = 0.220 (p> 0.05) based on the MMAS questionnaire, this indicates that the administration of drug information had no effect on the level of adherence to antidiabetic use in DM patients at Ketapang Sokaraja Kulon. Keywords: Blood Sugar, Diabetes Mellitus, Drug Information